The Role of Probiotics in Animal Health - Dr. Sandra Edwards (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2022)
Probiotics, defined as live microorganisms that confer health benefits when administered in adequate amounts, have garnered considerable attention in veterinary medicine for their potential to enhance animal health and performance. This review explores the multifaceted roles of probiotics in various animal species, emphasizing their mechanisms of action, efficacy in disease prevention, and modulation of the gut microbiota. Firstly, probiotics exert their beneficial effects through several mechanisms, including competitive exclusion of pathogenic bacteria, enhancement of gut barrier function, and modulation of immune responses. These actions contribute to reduced incidence and severity of gastrointestinal disorders such as diarrhea and colitis, commonly observed in livestock and companion animals.